Pengaruh Gaya Kepemimpinan Terhadap Motivasi Kerja Pegawai Di Kelurahan Bugel Kecamatan Polokarto - Suryani, Lilis; Anfas, Anfas (Journal of Management Branding, 2024)
This research aims to find out how leadership style influences employee motivation at work. A The purpose of this study is to determine how leadership style affects workers' motivation at work. Research on the impact of leadership style on work motivation was conducted in Bugel Village, Polokarto District, using a quantitative methodology. Thirty employees made up the sample size after the Slovin formula and proportionate random sampling technique were applied. The Pegawai Bugel District is home to the population. For the purposes of this study, all Bugel Village employees served as samples. Coefficient of determination, t test, F test, and basic regression analysis are examples of data processing techniques. It is well recognized from the study method and data presentation that a leader's style influences employee performance motivation, which in turn may inspire employees to produce higher- quality work. This is evident from the fact that Bugel District's leadership style has a major impact on employees' motivation at work